Aplikasi Lama Induksi SIPLO (Sistem Intensifikasi Potensi Lokal) Dan Waktu Pruning Pada Tanaman Tomat (Lycopersicum esculentum Mill) Sebagai Upaya Peningkatan Hasil Dan Kualitas - Eka Rizkiyani Nugrahayyu; Sugiarto Sugiarto; Abdul Basit (AGRONISMA, 2021)
SIPLO (Local Potential Intensification System) is local potential through electric induction to balance positive and negative soil charges which play an important role in the process of supplying nutrients in the soil. Pruning is done so that the plants will bear fruit more quickly and no nutrients will be fixed on the fruit, and are useful for plant growth and tomato production. The research was conducted to see the effect of the combination of SIPLO induction application and pruning time on the yield and quality of tomato plants. The design used is factorial RAK which consists of two factors. The first factor was the duration of SIPLO induction consisting of four levels (no induction, 40 minutes of ciplo induction, 80 minutes of ciplo induction, and 120 minutes of ciplo induction). The second factor is trimming consisting of four levels (no pruning, 30 days of pruning, 40 days of pruning, and 50 days of pruning). The results showed that the treatment of cyplo induction time and pruning time increased the yield and quality of tomato plants. Tomato fruit weight and total dissolved solids (TPT) gave a maximum of 27759.47 kg / ha and 5.37 0Brix, respectively.